2010
DOI: 10.1080/13102818.2010.10817898
|View full text |Cite
|
Sign up to set email alerts
|

Determination ofPseudomonas PutidaLive Cells with Classic Cultivation and Staining with “Live/Dead Baclight Bacterial Viability Kit”

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…After the EPS extraction, the remaining algae were collected and regarded as the algae without EPS. The TEM characterization, Live/Dead test 62 , and 96 h growth assay were performed to assess the potential effect of the EPS extraction on the algae. As one of the major components of EPS, the secretion kinetics of extracellular protein from the untreated and EPS-extracted algal cells in the absence and presence of the AgNPs and Ag + (from AgNO 3 ) were also determined.…”
Section: Methodsmentioning
confidence: 99%
“…After the EPS extraction, the remaining algae were collected and regarded as the algae without EPS. The TEM characterization, Live/Dead test 62 , and 96 h growth assay were performed to assess the potential effect of the EPS extraction on the algae. As one of the major components of EPS, the secretion kinetics of extracellular protein from the untreated and EPS-extracted algal cells in the absence and presence of the AgNPs and Ag + (from AgNO 3 ) were also determined.…”
Section: Methodsmentioning
confidence: 99%
“…After cultivation on solid rich medium, these cells give the slow growing colonies, which are visible after 48 h. These facts suggest that some of the red cells, which have been marked as dead, are viable and could restore their normal functions, giving colonies that emerge later. We proved the possibility of some sub lethal membrane damages which could bring to red staining and confusion in the results interpretation [31].…”
Section: The Behavior Of Pseudomonas Putida Cells On Thin Zno Film Is Verymentioning
confidence: 81%
“…It was reported that viable P . putida (ATCC 12633) cells were stained by propidium iodide suggesting that the use of LIVE/DEAD BacLight Bacterial Viability kit may give a confusing result in determining live cells [50]. We propose that additional studies like TEM, changes in membrane fluidity, changes in membrane potential and changes in membrane phospholipid composition will be required to clarify the level of membrane damage in our viable but non-culturable bacterial cells subjected to desiccation-rehydration process.…”
Section: Discussionmentioning
confidence: 99%